The apical transmembrane protein Crumbs functions as a tumor suppressor that regulates Hippo signaling by binding to Expanded - Ling, Chen (National Academy of Sciences, 2010)
The Hippo signaling pathway regulates organ size and tissue homeostasis from Drosophila to mammals. At the core of the Hippo pathway is a kinase cascade extending from the Hippo (Hpo) tumor suppressor to the Yorkie (Yki) oncoprotein. The Hippo kinase cascade, in turn, is regulated by apical membrane-associated proteins such as the FERM domain proteins Merlin and Expanded (Ex), and the WW- and C2-domain protein Kibra. How these apical proteins are themselves regulated remains poorly understood. Here, we identify the transmembrane protein Crumbs (Crb), a determinant of epithelial apical-basal polarity in Drosophila embryos, as an upstream component of the Hippo pathway in imaginal disk growth control. Loss of Crb leads to tissue overgrowth and target gene expression characteristic of defective Hippo signaling. Crb directly binds to Ex through its juxtamembrane FERM-binding motif (FBM). Loss of Crb or mutation of its FBM leads to mislocalization of Ex to basolateral domain of imaginal disk epithelial cells. These results shed light on the mechanism of Ex regulation and provide a molecular link between apical-basal polarity and tissue growth. Furthermore, our studies implicate Crb as a putative cell surface receptor for Hippo signaling by uncovering a transmembrane protein that directly binds to an apical component of the Hippo pathway.